Seed germination characteristics as affected by interaction of moisture stress and temperature in sethoxydim-resistant biotype of goosegrass (Eleusine indica (L.) Gaertn.) from Malaysia - Chuah, Tse Seng; Hiew, Chee Nam; Nursyafiqah Izzati Norzaidi,; Goh, Sunny Eng Giap (Penerbit Universiti Kebangsaan Malaysia, 2023)
Understanding temperature and moisture stress that influence sethoxydim-resistant (R) goosegrass (Eleusine indica) germination is crucial for effective weed control, but little research has been done on the impact of these environmental factors on germination of the R goosegrass biotype. This research aims to confirm sethoxydim resistance in goosegrass and to examine interaction effects of different temperatures and water potentials on germination of the R goosegrass biotype. Dose–response tests showed that the R goosegrass biotype exhibited high resistance level to sethoxydim with 17-fold. In laboratory bioassays, the R goosegrass biotype germinated by 88-100% at 35 °C with water potentials ranging from 0 to -0.80 MPa, but no seed germination occurred at 10 °C and 40 °C under all water potential treatments. With rising water potentials from 0 to -0.80 MPa, seed germination at 15 to 30 °C decreased markedly. The time it took to achieve 50% seed germination (T50) increased drastically when decreasing temperature from 35 to 15 °C. The T50 at 20 to 30 °C also increased as the water potential increased from -0.20 to -0.80 MPa. At 35 °C, however, the water potential level had no impact on T50, implying that the R goosegrass biotype seed is water stress tolerant at 35 °C. The base temperature and base water potentials estimated were 10.6 °C and -1.28 MPa, respectively. These findings can help in determining the optimal time to apply pre-emergent and early post-emergent controls when a large proportion of R goosegrass biotype have already germinated or emerged.